CHEST WALL HEMANGIOMA: A DIFFICULT PREOPERATIVE DIAGNOSIS - Macedo, Amarilio; Fadel, Elie; Paul, Jean François; de Montpreville, Vincent; Dartevelle, Philippe G. (Clinical and Biomedical Research, 2020)
We report a case that presents a diagnostic challenge in a 22 year-old female. CT-Scan and MRI showed a soft-density mass (12 cm) causing middle arch erosion of the fifth rib. In this rapidly-growing chest wall tumor a surgical-biopsy was very hemorrhagic and frozen section was unabled to disclose a sarcoma. Angiography and embolization of the feeding arteries were done. The final histopathology pointed out hemangioma. Complete resection was performed without prosthesis interposition. We emphasize two points regarding vascular chest wall tumors: (1) its possibility to mimick a sarcoma, so the surgical planning demands preoperative diagnosis; (2) the positive role of embolization in large and fast-growing lesions.